Correlates of Arrhythmia Recurrence After Hybrid Epi- and Endocardial Radiofrequency Ablation for Persistent Atrial Fibrillation. (August 2017) - Bulava, Alan; Mokracek, Ales; Hanis, Jiri; Eisenberger, Martin; Kurfirst, Vojtech; Dusek, Ladislav
Abstract : Background—: Long-term efficacy of catheter-based treatment of persistent atrial fibrillation is unsatisfactory. Minimally invasive surgical ablation techniques have been developed recently, but their efficacy has never been systematically tested. Methods and Results—: Seventy patients (median age, 63.5 years) with persistent atrial fibrillation underwent epicardial thoracoscopic radiofrequency pulmonary vein isolation, linear ablation, Marshal ligament disruption, and exclusion of the left atrial appendage. The procedure was followed by electroanatomic mapping and ablation (EAM) 2 to 3 months later. Only 76% of patients were in normal sinus rhythm at the beginning of EAM. All 4 pulmonary veins and the left atrium posterior wall were found isolated in 69% and 23% of patients, respectively. Arrhythmia-free survival off antiarrhythmic drugs 12 months after EAM was 77%. Using previously ineffective antiarrhythmic drugs and reablation procedures, arrhythmia free-survival increased to 97% during follow-up (mean, 936±432 days; range, 346–1509 days). The majority of arrhythmia recurrences occurred during the first 12 months after EAM. In a multivariable-adjusted estimates, left atrium volume >165 mL, absent normal sinus rhythm at admission for EAM, and inducibility of any sustained tachyarrhythmia at the end of EAM procedure were identified as independent correlates of atrial fibrillation recurrence. Conclusions—: Our report demonstrated that the majority of patients after epicardial ablation, using bipolar radiofrequency instruments, required endocardial catheter ablation to complete the linear ablation lesions and a significant proportion of patients required spot-ablations to complete electric pulmonary vein isolation. Noninducibility of any arrhythmia after a staged hybrid procedure seemed to be the strongest correlate of long-term arrhythmia-free survival. Clinical Trial Registration—: URL:www.ablace.cz . Unique identifier: cz-060520121617.